EFFECT OF MOTIVATON AND CREATIVITY ON STUDENTS’ PSYCHOMOTOR ABILITY - Muhamad Arpan; Dewi Sulistiyarini; Danar Santoso (JETL (Journal of Education, Teaching and Learning), 2016)
This research aims to determine: (1) the effect of motivation on students’ psychomotor ability; (2) the effect of creativity on students’ psychomotor ability; (3) the effect of motivation and creativity as in aggregate on students’ psychomotor ability; and (4) the contribution of motivation and creativity on students’ psychomotor ability in the subject of Web Programming. This research is an ex-post facto type. The population was sixth semester students of TIK Education Research Program of PGRI Pontianak totaling 217 students. The sample was 135 students with proportional random sampling techniques that determined by the Issac and Michael table. Data collection using a questionnaire. The data was analyzed using regression analysis to test the hypotheses. The results showed that: (1) motivation has a positive and significant effect on students’ psychomotor Ability; (2) creativity has a positive and significant effect on students’ psychomotor Ability; (3) motivation and creativity as in aggregate had a positive and significant effect on students’ psychomotor Ability with 68.88%; and (4) the contribution of motivation is 12.5% and creativity is 32.5% on students’ psychomotor Ability in the subject of Web Programming.